Meta-Analysis Of The Effect Of Using A Student-Centered Learning Approach On Student Physics Learning Outcomes - Fachreza, Ardian; Desnita, Desnita; Putra, Amali; Satria Dewi, Wahyuni (Jurnal Pendidikan Tambusai, 2023)
This study aims to determine the effect size of the effect of a student-centered learning approach on student physics learning outcomes based on the type of approach (Scientific approach & Contextual Teaching Learning (CTL) approach); determine the effect size of the effect of a student-centered learning approach on student physics learning outcomes based on physics material units and determine the effect size of the effect of a student-centered learning approach on student physics learning outcomes based on physics grade levels. This research method is a Meta-analysis research that summarizes various studies using a quantitative approach. To calculate the Effect Size of the articles studied using the Pre-Post Contrast and Group Contrast formulas. Based on the results and meta-analysis research it can be concluded that, the effect of a student-centered learning approach is very effective on student physics learning outcomes based on the type of scientific approach and contextual teaching learning (CTL) approach with an effect size of 1.484 and 2.253 respectively, both classified as very high. The effect of a student-centered learning approach on student physics learning outcomes based on subject matter, provides the most effective influence on Straight Motion Kinematics material with an effect size of 4.359 and is classified as very high. The effect of the student-centered learning approach on student physics learning outcomes based on class level, provides the most effective influence on class X and class XI with each effect size of 1.834 and 1.502 with very high classified.